A post hoc analysis on hospitalization risk in Asian patients with schizophrenia switching to once-monthly paliperidone palmitate from oral antipsychotics. (2nd November 2019) - Li, Nan; Zhuo, Jian Min; Turkoz, Ibrahim; Mathews, Maju; Feng, Yu; Tan, Wilson
ABSTRACT: Background : In this post hoc analysis in patients recently diagnosed (≤5 years) with schizophrenia, the effect on hospitalization risk after switching from oral antipsychotic to once-monthly paliperidone palmitate (PP1M) was evaluated. Research design and methods : Change in hospitalization risk following PP1M initiation among patients switching from oral antipsychotics was assessed using prescription sequence symmetry analysis. Hospitalization risk was expressed as an adjusted sequence ratio (ASR) of the number of patients hospitalized prior to PP1M initiation/post PP1M initiation. Cumulative distribution of the time to hospitalization was estimated by the Kaplan-Meier method and symmetry of distribution was assessed using log-rank test. Hazard ratio and 95% CI were calculated using the Cox proportional hazard model. Results : The number of patients hospitalized after switching to PP1M: no change, 203/300 (67.7%); increase, 18/300 (6.0%); and decrease, 79/300 (26.3%). Following PP1M initiation, ASR (95% CI) was 3.56 (2.67, 5.33) suggesting asymmetry and a significant decline in hospitalization risk. Asymmetry in distribution of hospitalization events with significant (p ≤ 0.001) delay in time to hospitalization was also observed. Conclusion : Switching to PP1M treatment from oral antipsychotics is likely to be associated with a significant reduction in hospitalization risk along with a delay in time to hospitalization and rehospitalization.